49. THE IMPACT OF NEGATIVE EMOTIONS DURING CLINICAL PRACTICE AT HOSPITAL AND THEIR RESPONSES OF 4TH YEAR MEDICAL STUDENTS AT HANOI MEDICAL UNIVERSITY, YEAR 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the impact of negative emotions experiences encountered by 4th year medical students of Hanoi Medical University during clinical practice at the hospital and ways to cope.Methods: A cross-sectional descriptive study, combining quantitative and qualitative researchResults: Negative emotional experiences significantly impact students' physical and mental health, as well as their academic and social lives. In response, students primarily employ positive coping strategies like seeking support, though some adopt maladaptive methods such as avoidance and self-blame.Conclusion: Emotional experiences in clinical practice significantly affect medical students' health, social lives, and learning; therefore, understanding these impacts and equipping them with coping skills is crucial for their professional training.
Keywords: Emotion; Medical students; Clinical practice; Coping strategies.